SEC staff issues money market fund reform frequently asked questions. Issue 4 (2nd November 2015) - Murphy, Jack; Carroll, Brenden; Cohen, Stephen; Katz, Joshua; Goldberg, Justin
Abstract : Purpose: – To explain the background and details of the responses from the Staff of the Division of Investment Management of the US Securities and Exchange Commission (SEC) to certain frequently asked questions (FAQs) regarding the July 23, 2014 amendments to Rule 2a-7 and other rules that govern money market funds under the Investment Company Act of 1940 (1940 Act). Design/methodology/approach: – In July 2014, the SEC adopted sweeping amendments to Rule 2a-7 and other rules that govern money market funds under the 1940 Act (Amendments). The Amendments (i) require "institutional" money funds to operate with a floating net asset value (NAV), rounded to the fourth decimal place (e.g. $1.0000) and (ii) permit (and, under certain circumstances, require) all money funds to impose a "liquidity fee" (up to 2 per cent) and/or "redemption gate, " once weekly liquidity levels fall below the required regulatory threshold. The article briefly discusses the background and the events leading up to the FAQs and describes key responses from the Staff on a variety of issues. Findings: – The Amendments set forth sweeping changes to money fund regulation and will have a profound effect on the money fund industry. Although the most significant provisions of the Amendments – the floating NAV requirement and the imposition of liquidity fees and redemption gates – will not go into effect for two years, the changes to the industry will be apparent almost immediately. The FAQs provide clarity on a number of issues that are relevant to the money fund industry. Practical implications: – Money fund managers and boards of directors should begin assessing the potential impact of the Amendments and develop a schedule to come into compliance. Originality/value: – Practical guidance from experienced financial services lawyers.